2003
DOI: 10.1002/casp.721
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing homelessness research: trends, lessons and prospects

Abstract: This paper presents an overview of some of the key trends emerging from homelessness research to date, lessons to be learned, and some thoughts on the future prospects for homelessness research. Homelessness research draws on a number of academic disciplines, in an international context, and using a wide range of research methods. There is a significant theoretical and empirical research evidence base for understanding the nature and causes of homelessness, and a developing body of research on the impact of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 18 publications
(16 reference statements)
0
21
0
Order By: Relevance
“…Anderson 2003;Connolly 2000;Williams 2003). This literature does not provide a critical engagement with what it means to be a woman on the street.…”
Section: Introductionmentioning
confidence: 96%
“…Anderson 2003;Connolly 2000;Williams 2003). This literature does not provide a critical engagement with what it means to be a woman on the street.…”
Section: Introductionmentioning
confidence: 96%
“…54 Individual factors or characteristics have been categorized as: (a) predisposing factors (e.g., demographics and health beliefs); (b) enabling factors (e.g., family and community resources); and (c) need (e.g., symptoms and functioning). 21 Among homeless persons, identity could also have an impact on the utilization of services, in addition to individual characteristics. According to Osborne, 55 people who possess a strong homeless identity should be less inclined to use services.…”
Section: Discussionmentioning
confidence: 99%
“…20 Several authors have suggested conducting such longitudinal population studies in order to gain a better knowledge and deeper understanding of the usage trajectory of these services. [21][22][23] However, some long-term follow-up studies examining the utilization of services by different types of cohorts (i.e., not necessarily homeless people) have been published. For instance, research has been conducted on Americans using general health and mental health services over a 12-month period, 24 among persons presenting psychiatric disorders and using these services over 1 year, 25 and among users of emergency psychiatric services over 5 years.…”
Section: Longitudinal Studiesmentioning
confidence: 99%
“…For example, the concepts of structure and agency, and the interaction between the two, feature prominently in the UK homelessness literature (Anderson and Christian 2003;Clapham 2002Clapham , 2003 and theories from other disciplines, such as psychology, may also have a role in explaining individual experiences of homelessness (Anderson 2003). Such a micro-level analysis could not be developed in this paper but its centrality to a full understanding of the complexity of contemporary homelessness is acknowledged.…”
Section: Homelessness State Intervention and Models Of Welfare: Altementioning
confidence: 98%